STRATEGI PENGEMBANGAN BISNIS CAFE D’ TERAS FOOD AND DRINK : BLUE OCEAN STRATEGY - Nabilla Nurfitrianisda; Husni Shabri (Jurnal Manajemen Bisnis Syariah, 2024)
The main problem in the research is the decline in visitors to the D' Teras Food and Drink cafe in the last few months due to tight competition in the culinary business in Nagari Cubadak. The aim of this research is to determine the strategy for developing the D' Teras Food and Drink cafe business using the Blue Ocean Strategy approach.This type of research is field research with qualitative descriptive research methods. Data collection techniques use interviews. The data analysis technique uses Miles and Huberman with stages of data reduction, data presentation and drawing conclusions. as well as development strategy analysis tools using Blue Ocean Strategy.The research results show that the implementation of the four-step Blue Ocean Strategy framework is eliminating several menus that are rarely available and ordered by customers. Reducing the prices of Food and Drinks, which are still quite high. Increasing the menu to be more varied and unique, increasing the number of employees, more actively promoting the cafe via social media, and making the cafe decoration more attractive and aesthetic. Creating several supporting facilities, such as acoustic and karaoke equipment, parking lots that can protect vehicles from rainy and hot weather, and adding digital payment methods